On the use of tapered channels gas distributors to promote convection in PEM Fuel Cells - d’Adamo Alessandro (EDP Sciences, 2021)
Polymeric Exchange Membrane Fuel Cells (PEMFC) are promising power propulsion systems for the decarbonization of the transportation sector. Despite being a well-known method for the direct production of electric current from the reactants chemical energy, one of the major limitations to their large-scale industrial development are fluid dynamics and mass transport aspects, crucially limiting the electrochemistry rate under critical conditions. This is especially verified in PEMFC with serpentine-type gas distributors, for which such areas are identified in proximity of the gas channel bends where the dominant mechanism for species transport shifts from a convection-enhanced to a diffusion-limited one. An engineering method to enhance the convective transport in such deficient areas is the use of gas distributors with tapered channels, effectively forcing the flow in diffusive media and improving the reactants delivery rate and products removal. A numerical analysis is presented on a limited domain representing a section of a serpentine gas distributor. A multi-dimensional CFD study is carried out comparing conventional-type and tapered channel distributors, evaluating the combined effect of pressure losses, catalyst layers utilization, flow regime in anisotropic diffusion media and convection/diffusion balance via a non-dimensional analysis. The study covers various inlet Reynolds numbers and in-plane permeability of porous materials for two diffusion media thicknesses, with the aim to extend the generality of the study. Conclusions based on the simulation results outline channel tapering as a very effective way to improve the power density of PEMFC, although an energetic cost/benefit analysis indicates a reduced cell efficiency.